2014
DOI: 10.1021/jz501987r
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Evaporation and Solvation of Helium Atoms at the Surfaces of Protic and Hydrocarbon Liquids

Abstract: Atomic and molecular solutes evaporate and dissolve by traversing an atomically thin boundary separating liquid and gas. Most solutes spend only short times in this interfacial region, making them difficult to observe. Experiments that monitor the velocities of evaporating species, however, can capture their final interactions with surface solvent molecules. We find that polarizable gases such as N2 and Ar evaporate from protic and hydrocarbon liquids with Maxwell-Boltzmann speed distributions. Surprisingly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…It has been found that the He atoms' velocity distribution is shifted to fractionally faster velocities as compared to a Maxwell-Boltzmann velocity distribution of He atoms at the temperature of the liquid surface. This result has qualitatively also been obtained in the experimental studies by Nathanson and co-workers [8], but the effect is more pronounced in the liquid jet experiments than in the simulations. We have also established that faster He atoms have a slight preference to evaporate along the surface normal, i.e.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…It has been found that the He atoms' velocity distribution is shifted to fractionally faster velocities as compared to a Maxwell-Boltzmann velocity distribution of He atoms at the temperature of the liquid surface. This result has qualitatively also been obtained in the experimental studies by Nathanson and co-workers [8], but the effect is more pronounced in the liquid jet experiments than in the simulations. We have also established that faster He atoms have a slight preference to evaporate along the surface normal, i.e.…”
Section: Discussionsupporting
confidence: 85%
“…These fits consistently yielded distributions of evaporated He atoms which are fractionally faster than a thermal 298 K distribution, with an average translational energy of (1.05 ± 0.03) × 2RT. The obtained average translation energies are a convenient measure to compare our data to the experimental work by Nathanson and co-workers, who find an average kinetic energy of He atoms evaporating from 295 K liquid dodecane of 1.14 × 2RT [8], albeit these data are for He atoms evaporating from a cylindrical jet. To allow for a better comparison, we have weighed our data by sin(Â) −1 where  is the polar angle of the evaporating He atoms with respect to the surface normal.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…This behavior stands in contrast to larger and more polarizable species such as Ar, N 2 , O 2 , H 2 O, CO 2 , HCl, and HNO 3 , which evaporate with flux-weighted average energies of 2RT liq consistent with a MB energy distribution for a liquid at temperature T liq . 6,9 We recently found that the He speed distributions depend on the nature of the solvent molecules, with average kinetic energies ranging from 1.14 × 2RT liq for He evaporation from dodecane to 1.7 × 2RT liq from a 7.5 M LiBr/ H 2 O solution. 6 Detailed balancing of the incoming and outgoing fluxes implies that He atoms must preferentially dissolve at higher kinetic energies as well.…”
Section: ■ Introductionmentioning
confidence: 99%